2010
DOI: 10.4081/jear.2010.161
|View full text |Cite
|
Sign up to set email alerts
|

Using a kairomone-based attracting system to enhance biological control of mealybugs (Hemiptera: Pseudococcidae) by Anagyrus sp. near pseudococci (Hymenoptera: Encyrtidae) in Sicilian vineyards

Abstract: -The "potato trap" technique was applied for the first time in Italian (Sicily) vineyards in an attempt to assess: a) the impact of the kairomonal activity of the vine mealybug sex pheromone (S)-(+)-lavandulyl senecioate (LS) on the parasitism of mealybugs by the encyrtid Anagyrus sp. near pseudococci, b) the influence of two commonly used insecticides on the parasitization activity of A. sp. near pseudococci towards mealybugs, and c) the efficiency of the release of A. sp. near pseudococci in enhancing parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…In southern Italian (Sicily) vineyards, treatments with chlorpyrifos-methyl significantly affected 2013The classification of pesticide modes of action is presented according to the standards of the Insecticide Resistance Action Committee (IRAC 2016) the parasitization potential of Anagyrus sp. near pseudococci (Girault) (Mansour et al 2010b), one of the most common parasitoids of the vine mealybug in the Mediterranean basin (Franco et al 2009;Mansour et al 2017a;Suma et al 2012a, b). Twenty-four hours after tarsal contact, chlorpyrifos-methyl was shown to be harmful (toxicity category 4 of the International Organization for Biological Control), causing 100% mortality to adult A. sp.…”
Section: Side Effects On Natural Enemiesmentioning
confidence: 99%
See 3 more Smart Citations
“…In southern Italian (Sicily) vineyards, treatments with chlorpyrifos-methyl significantly affected 2013The classification of pesticide modes of action is presented according to the standards of the Insecticide Resistance Action Committee (IRAC 2016) the parasitization potential of Anagyrus sp. near pseudococci (Girault) (Mansour et al 2010b), one of the most common parasitoids of the vine mealybug in the Mediterranean basin (Franco et al 2009;Mansour et al 2017a;Suma et al 2012a, b). Twenty-four hours after tarsal contact, chlorpyrifos-methyl was shown to be harmful (toxicity category 4 of the International Organization for Biological Control), causing 100% mortality to adult A. sp.…”
Section: Side Effects On Natural Enemiesmentioning
confidence: 99%
“…Buprofezin applied at 1 L ha −1 is one of the most commonly used insecticides for controlling the vine mealybug in vineyards in Italy (Mansour et al 2010b) similarly to North American (California and Mexico) vineyards, where a foliar application in late spring or early summer is incorporated in most insecticide programs (Daane et al 2012). In California vineyards, buprofezin-based treatments have been shown to be the most effective in reducing cluster damage caused by P. ficus infestations (Daane et al 2006).…”
Section: Efficacy Against Vine and Citrus Mealybugsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the performance of this parasitoid can be enhanced by applying a kairomone-based attracting system in vineyards. Indeed, Mansour et al (2010b) showed that the application of VM sex pheromone as kairomone increased parasitism rates of mealybugs by anagyrus sp. near pseudococci within Sicilian vineyards.…”
Section: Mealybugs Of High Economic Importancementioning
confidence: 99%